Twentieth-Century Analytic Philosophy: LUDWIG WITTGENSTEIN. (Columbia History of Western Philosophy, 1999)
A section from chapter 8 of the book "The Columbia History of Western Philosophy," edited by Richard H. Popkin is presented. It focuses on philosopher Ludwig Wittgenstein. It compares Wittgenstein with Socrates, who are said to be both austere, intensely self-critical and driven by a relentless dedication to philosophy. It also provides information on the two phases of the philosophical career of Wittgenstein.